2005
DOI: 10.1111/j.0014-3820.2005.tb01049.x
|View full text |Cite
|
Sign up to set email alerts
|

Size as a Line of Least Evolutionary Resistance: Diet and Adaptive Morphological Radiation in New World Monkeys

Abstract: Abstract. New World monkeys (NWM) display substantial variation (two orders of magnitude) in body size. Despite this, variation in skull size and associated shape show a conserved allometric relationship, both within and between genera. Maximum likelihood estimates of quantitative ancestral states were used to compare the direction of morphological differentiation with the phenotypic (p max ) and genetic (g max ) lines of least evolutionary resistance (LLER). Diversification in NWM skulls occurred principally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
206
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(219 citation statements)
references
References 41 publications
9
206
3
1
Order By: Relevance
“…In addition to absolute differences in body and skull size, we found positive allometry in skull shape with respect to skull size across bats that consume animal prey. This adds to a body of work stressing the role of allometry in underlying morphological diversity in the mammalian feeding apparatus [17,[60][61][62][63][64][65]. In carnivorous bats, larger sizes are associated with cranial and mandibular traits that increase bite force, gape and jaw closing speed: a taller sagittal crest provides larger attachment area for the temporalis muscle; a longer rostrum produces a wider gape that can accommodate larger prey, and enables faster jaw closure in prey capture [66].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to absolute differences in body and skull size, we found positive allometry in skull shape with respect to skull size across bats that consume animal prey. This adds to a body of work stressing the role of allometry in underlying morphological diversity in the mammalian feeding apparatus [17,[60][61][62][63][64][65]. In carnivorous bats, larger sizes are associated with cranial and mandibular traits that increase bite force, gape and jaw closing speed: a taller sagittal crest provides larger attachment area for the temporalis muscle; a longer rostrum produces a wider gape that can accommodate larger prey, and enables faster jaw closure in prey capture [66].…”
Section: Discussionmentioning
confidence: 99%
“…Even though facial patterning is not related to size, we confirmed that larger primates, which have a larger facial nucleus, tend to have more expressive faces. Evolution of differences in body size can constitute a line of least resistance that could facilitate the evolution of differences in these and many other functional traits [21]. The evolution of larger bodies, potentially coupled with increased reliance on vision for other ecological tasks (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they noted that some explicit phylogenetic studies-e.g., of primates such as Old and New World monkeys-actually "did fail to recover or recovered only a weak relationship between ecological variation, including differences in diet, and cranial form (e.g., McBrayer, 2004;Cardini and Elton, 2008;Jones and Goswami, 2010;Perez et al, 2011)." In addition, in some studies dietary variables could predict a great proportion of variation of cranial shape, but only when phylogeny was ignored, because when it was taken into account many fewer anatomical features remained associated to ecology (e.g., Perez-Barberia and Gordon, 1999;Marroig and Cheverud, 2005). Based on the results of their lemur phylogenetic study, Baab et al (2014Baab et al ( , p. 1472 thus stated that "overall, lemur cranial morphology retains a strong phylogenetic signal... the correlation between diet and cranial form is weak when the underlying phylogeny is taken into account, a pattern also documented in other vertebrate lineages."…”
Section: An Overview Of Empirical Etho-eco-morphological Studies Acromentioning
confidence: 99%